The relationship between habitat quality and the diversity of phytoplankton, zooplankton, and nekton in mangrove ecosystems of Bawean Island, Indonesia - CATUR RETNANINGDYAH; ENDANG ARISOESILANINGSIH; VIKY VIDAYANTI; QATHRUNNADA SALSABILA; PURNOMO PURNOMO (Biodiversitas Journal of Biological Diversity, 2024)
Abstract. Retnaningdyah C, Arisoesilaningsih E, Vidayanti V, Salsabila Q, Purnomo P. 2024. The relationship between habitat quality and the diversity of phytoplankton, zooplankton, and nekton in mangrove ecosystems of Bawean Island, Indonesia. Biodiversitas 25: 3017-3026. Mangrove ecosystem consists of biotic and abiotic components that interact with each other to form a food chain. This study aims to analyze the relationship between the diversity and abundance of phytoplankton, zooplankton, and nekton and water quality, human activities, and carbon stock in the mangrove ecosystem in Bawean Island. Data was collected from 11 sampling locations across the island. At each location, we observed the diversity of phytoplankton, zooplankton, and nekton and carbon stock of mangroves along with data of water quality (salinity, pH, dissolved oxygen/DO, biochemical oxygen demand/BOD, nitrate, orthophosphate, dihydrogen sulfide/H2S, dissolved lead/Pb) and human activities based on the hemeroby index. The research results showed that the level of DO, H2S, nitrate, and orthophosphate did not meet the quality standard according to the Indonesian government. The level of disturbance from human activities varied from ?-mesoherobic to metahemerobic categories. Human activities and higher levels of H2S in waters had a negative relationship with mangrove ecosystem carbon stock and the diversity and taxa richness of phytoplankton, zooplankton, and nekton. Phytoplankton diversity had a positive relationship with zooplankton, while zooplankton diversity had a positive relationship with nekton. High carbon stock in the mangrove ecosystem will likely increase the diversity of phytoplankton, zooplankton, and nekton. The result of this study implies that anthropogenic activities need to be controlled to improve the Bawean Island mangrove ecosystem services.